Obtaining cyclopentanone from acidic wastewater of caprolactam production - I. V. Tsvetkova (Uralʹskij federalʹnyj universitet imeni pervogo Prezidenta Rossii B.N. Elʹcina, 2020)
It has been shown that adipic acid released from the by-products of caprolactam production is a promising raw material for the production of cyclopentanone. The thermal stability of calcium adipate was investigated by the derivatographic method and the conditions were selected that ensure the yield of at least 50% of the target cyclopentanone with a purity of at least 99%.